ANALISIS LOYALITAS PEGAWAI FUNGSIONAL PENGELOLA PENGADAAN BARANG/JASA PEMERINTAH DI DAERAH ISTIMEWA YOGYAKARTA - saiful saiful (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine the effect of training and compensation on the loyalty of functional employees managing goods/ services procurement in D.I Yogyakarta with motivation as an intervening variable. The subjects in this study were 30 people who selected by census techniques toward ASN employees with JFT status in government procurement of goods/ services in the D.I Yogyakarta, both the ASN Central Ministry and ASN in the Regency. The technique of collecting data use a questionnaire. Data analysis techniques use PLS. The results of the study show that: (1) There is a positive and significant influence between training and work motivation; (2) There is a positive and significant influence between compensation and work motivation; (3) There is a positive and significant influence between training and compensation for work motivation; (4) There is a positive and significant influence between training and employee loyalty; (5) There is a positive influence between compensation and loyalty; (6) There is a positive and significant influence between motivation and employee loyalty and (7) There is the positive influence of training, compensation and motivation on employee loyaltyÂ Keywords: Training, Compensation, Loyalty, Motivation